1981
DOI: 10.1063/1.440949
|View full text |Cite
|
Sign up to set email alerts
|

Optical spectra and Zeeman effect for Er3+ in LuPO4 and HfSiO4

Abstract: The absorption spectra of Er3+ diluted in LuPO4 and HfSiO4 crystals have been measured from 6000 to 28 000 cm−1 at liquid He and N2 temperatures. Zeeman spectra were obtained in the visible region. The transitions were assigned and fitted to a semiempirical Hamiltonian with ten adjustable parameters. Satisfactory fits were obtained including reasonable agreement between calculated and measured g values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Similar measurements involved cerium, neodymium, dysprosium, erbium, ytterbium and uranium at low abundance in single crystals [7]. Optical studies were made by Hayhurst et al [8,9] on erbium, praseodymium and neodymium in the phosphates of yttrium and lutetium. The g-values for a number of ions with doublet ground states in these two phosphates are given in Table 1.…”
Section: Diluted Compoundsmentioning
confidence: 93%
“…Similar measurements involved cerium, neodymium, dysprosium, erbium, ytterbium and uranium at low abundance in single crystals [7]. Optical studies were made by Hayhurst et al [8,9] on erbium, praseodymium and neodymium in the phosphates of yttrium and lutetium. The g-values for a number of ions with doublet ground states in these two phosphates are given in Table 1.…”
Section: Diluted Compoundsmentioning
confidence: 93%
“…Among them Pb 2 P 2 O 7 , PbO, PbO+PbF 2 , X 2 Mo 3 O 10 , (X=Li, K), X 2 CO 3 :MoO 3 (X=Li, Na) were tested and indeed 2-10 mm single crystals, occasionally even slightly larger ones, were successfully grown 1,[5][6][7][8][9][10][11][12][13][14] . Such crystals were not appropriate for industrial applications but were good for research, and it was showed that orthophosphates activated with lanthanides are efficient scintillators 3,15 .…”
Section: Introductionmentioning
confidence: 99%
“…9 Similar ground CFS was found for Nd 3+ ions in scheelite and Zircon-type NMO 4 hosts, [10][11][12] or for other Re 3+ Kramers ions in solid matrices. [13][14][15] As a result, the EPR spectra of the Nd 3+ ions measured at high frequencies ͑3-10 cm −1 ͒ and low temperatures are expected to be well described by a spin Hamiltonian ͑SH͒ with an effective spin one-half. Due to its increased resolution, the HF-EPR spectroscopy allows a higher accuracy in the g-factor determination.…”
Section: Study Of the Ground Multiplet Of Kramers Rare Earth Ions In mentioning
confidence: 99%